The Teenage Brain and Technology (LEARNing Landscapes, 2011)
The teenage brain is experiencing amazing transformations which set into motion unprecedented academic and emotional growth. As the brain is changing, technology works as a powerful influencer, sculpting and molding the mind. Computerbased instruction, in particular, is impacting the teenage brain as a motivator, tutor, and prolific source of information. Research synthesized from the fields of neuroscience, education, psychology, and technology inform and strengthen pedagogy for teaching secondary students.
Keywords: teenage; brain; academic; emotional; growth; technology; mind; coputerbased instruction; pedagogy; neuroscience; psychology; education